Relationship of the Knowledge Level with the Quality of Life of Diabetes Mellitus Patients at Pasar Merah Public Health Center Medan in 2023 - Rofiana, Silvy Agustin; Lubis, Marlina Elfa; Bestari, Ramadhan; Lubis, Ichwan Alamsyah; Ansari, Zaim (PT Inovasi Pratama Internasional, 2025)
Diabetes mellitus can affect almost all groups of people around the world, the number of diabetes mellitus patients according to data from the International Diabetes Federation (IDF) in 2021, 1 in 10 adults aged 20 to 79 years worldwide will suffer from diabetes. In addition, diabetes causes the death of 6.7 million people or one every five seconds. In the world, China has the highest number of adults with diabetes. 140.87 million people in China had diabetes in 2021. This study aims to determine the relationship between the level of knowledge of people with diabetes mellitus and their quality of life. This study uses a quantitative or analytical research design with a cross-sectional approach. The data used is a questionnaire. Univariate and bivariate analysis using chi square statistical test. The chi square test obtained a P value of 0.021, which is (p<0.05), so that it can be stated, namely H0 is rejected while H1 is accepted, which indicates that there is a meaningful relationship between the level of knowledge and quality of life in patients with diabetes mellitus, and in the spearmen test, a correlation of sig (2 tailed) 0.006 is obtained, namely (p<0.05), which means that a significant correlation is obtained between the two variables tested.